Paclitaxel Release from Polyether-Anhydrides Prepared with UV-Curing Process - Anxin Dong; Tao Zhang (International Journal of Polymer Science)
Polyanhydrides have been used as drug delivery systems to achieve a long-term delivery due to its hydrophobicity and surface erosion degradation behavior. In order to develop a simple, economical, and rapid approach to synthesize polyanhydrides, we prepared a series of polyether-anhydride membranes composed of different mass fractions of sebacic acid, polyethylene glycol dimethacrylate, and poly(tetramethylene oxide) dimethacrylate by ultraviolet curing process. The chemical structure and thermal properties of target polyanhydrides were characterized, while the paclitaxel releases from the polymer matrix were evaluated by HPLC. The results demonstrated that the UV-curing process is a good method to synthesize the target polymers in a short time, and the paclitaxel release procedure can be controlled by changing the component in the copolymers.